The Impact of Skincare Short Video Promotion at TikTok For You Page (FYP) to the Skincare Product Purchase Decision - Alfreya Shahla Witono; Fitri Aprilianty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
TikTok is the most social media used to guide people to purchase skincare products. In Indonesia, skincare is also having positive trends and perception in terms of skincare short video promotion in the For You Page (FYP). Recently, people give their negative perceptions regarding skincare short video promotion on TikTok FYP that makes people not directly trust it. This research intends to identify the TikTok user perception regarding the skincare short video promotion in TikTok FYP and understand how the promotion of skincare short videos on the TikTok FYP influences the decision to purchase skincare products. Research conducted through semi-structured interview and survey with 224 respondents, analyzed with open coding, descriptive statistics, and PLS-SEM. It shows that video that give enjoyment, usefulness, and easiness will be perceived positively, but video with potential of functional, information, and time-loss risk will be perceived negatively. Purchase Decision of skincare product are driven by Perceived Ease of Use and Trust of TikTok short video, also product promo. This finding will give insights to skincare company and affiliators about factors that lead TikTok users to purchase skincare product from short video.